Pengaruh Variasi Tes terhadap Motivasi dan Prestasi Belajar pada Mata Pelajaran Agama Kristen - Jessintha Filardin Laukapitang; Hemi D.Bara Pa; Delsi Oktoviana Oematan; Yasinta Emalia Waang; Jeanne Paula Konay; Agustina Ha’e; Deciana Mese Baok; Yakob Pai Tiba; Korne Amelia Haba Ito (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
This study aims to examine the impact of test variations on students’ motivation and academic achievement in Christian Religious Education subjects. Traditional evaluations that focus only on cognitive aspects often fail to capture students' full spiritual and character development. Using a qualitative descriptive approach through literature review, this article emphasizes the importance of varied assessmentssuch as written tests, oral exams, practical applications, service projects, portfolios, and personal faith reflectionsin creating meaningful, contextual, and transformative evaluations. The findings indicate that diverse testing methods enhance students’ learning motivation by accommodating different learning styles and have a positive effect on academic achievement, not only in knowledge mastery but also in the application of Christian values in daily life.